Support me in the good times too: Interpersonal emotion regulation, perceived social support, and loneliness among mothers of children with autism spectrum disorder. (February 2023) - Laslo-Roth, Roni; George-Levi, Sivan; Ben-Yaakov, Lital
Although loneliness is an experience that mothers of children with autism spectrum disorder (ASD) may face, it has not been widely explored. Having a supportive social environment that is also effective in emotion regulation may provide feelings of security necessary for one to feel less lonely. The present study examined loneliness levels among mothers of children with ASD (vs. without ASD) and explored interpersonal resources (interpersonal emotion regulation and perceived social support) that might contribute to reduced loneliness. One-thousand-seven-hundred-and-83 mothers of children (546 with ASD, 1, 237 without) completed a series of questionnaires. Mothers of children with ASD (vs. without ASD) reported higher levels of loneliness and lower levels of interpersonal emotion regulation efficacy for positive emotions and lower levels of perceived social support. A serial mediation model indicated that interpersonal factors fully mediated the association between being a mother of a child with ASD (vs. without) and loneliness. Moreover, a moderation mediation model showed that the tendency to approach others in order to regulate positive emotions moderated the association between perceived efficacy of such regulation and mothers' loneliness. Interpersonal emotion regulation for positive emotions and perceived social support may contribute to reduced loneliness, especially among mothers of children with ASD.